Ultrasonic enhancement of separation azeotropic mixtures via single distillation column - Mahdi, Taha (2013)
The separation of azeotropic mixtures is conventionally one of the most challenging tasks in industrial processes as their separation by a simple distillation is basically impossible. Vaporliquid equilibrium (VLE) equations with ultrasonic technique was based on a number of assumptions need to be built model on MATLAB software and compared the results with experimental work to validity the model. As a case study, the influence of ultrasonic intensity and frequency on the VLE of ethanol-ethyl acetate mixture was investigated, and a combination of five ultrasonic intensities (from 100 and 500 W/cm2) and three frequencies (from 25 to 70 kHz) were used. It is noted that with increase the ultrasound intensity and decrease the frequency can be improved the azeotropic point and relative volatility of the mixture. The results revealed that ultrasonic waves had the potential to enhance separation of azeotropic mixtures in a distillation column.